Pengaruh Teknologi Biometrik dan Jaminan Keamanan Cyber Terhadap Minat Transaksi Perbankan Online di Provinsi Lampung dalam Perspektif Islam - Mufatikhaturrohmah, Salma; Zulaikah (SAFE-Network, 2025)
The increased use of online banking has created new challenges in terms of security. Biometric technology and cybersecurity assurance are alternatives for increase user protection and trust. The purpose of this study is to analyze the influence of biometric technology and cyber security guarantees on the interest in online banking transactions of Lampung people in an Islamic perspective. This research applies a quantitative approach with primary data from 100 active online banking users respondents who are active online banking users. The analysis method applied is multiple linear regression. The results prove that biometric technology (β = 0.436; p < 0.001) and cyber security guarantee (β = 0.504; p < 0.001) have a positive and significant effect on transaction interest. Adjusted R value Square value of 0.594 shows the contribution of the independent variables by 59,4%. This research applies the theory of Technology Acceptance Model and Theory of Planned Behavior. In an Islamic perspective, security and trust are important factors in making financial decisions.